Experiences of emergency department nurses in providing palliative care to adults with advanced cancer: a systematic review protocol. (May 2016) - Revels, Amanda; Sabo, Brenda; Snelgrove-Clarke, Erna; Price, Sheri; Field, Simon; Helwig, Melissa
Abstract : Review questions/objectives: The objective of this review is to explore the experiences and perceptions of emergency department nurses in providing palliative care to adults with advanced cancer so as to contribute to the developing knowledge base on this phenomenon and, in turn, inform future practice and policy changes. Specifically, the review question for this qualitative review is as follows: what are the experiences and perceptions of emergency department nurses in providing palliative care to adults with advanced cancer?